Effects of water steam injection on direct injection diesel engine operating with partial loads - Parlak, A.; Ayhan, V.; Cesur, I. (ELSEVIER SCI LTD, 2013)
In the present study, a new method named 'water steam injection' is introduced as a measure to reduce NOx emissions. Required energy for producing water steam has been obtained from exhaust energy via the heat exchanger which was mounted to exhaust line of the engine. Main advantages of this method over the fumigation and emulsified fuel techniques, corrosive side effects of water on metallic surface have been eliminated by changing the phase of compressed hot water at 300 kPa and 133 degrees C to superheated vapour conditions at 101.325 kPa and inlet temperature. Optimum steam rate was obtained as 20% from the performance and the exhaust emissions points of view. The test results obtained from the partial load conditions are given comparatively. In a wide speeds and engine loads intervals, while the effective brake power and the efficiency increased, specific fuel consumption and NOx emission decreased.
Keywords: Diesel engine; Water steam; Injection; Performance; NOx; COMBUSTION CHARACTERISTICS; FUEL; EMULSION; IGNITION; SYSTEM; OIL; Energy & Fuels